Private clinic: identity and image in design to support rural communities at Sungai Limau, Yan, Kedah / Ts. Normaziana Hassan ... [et al.] - Hassan, Normaziana; Yusoff, Zaidi; Md Shahid, Shuhaila; Juhari, Muhammad Amin; Shafie, Muhammad Amer (Universiti Teknologi MARA, Kedah, 2024)
The design of a clinic is very important and should be emphasized, to provide comfort for patients. However, the existing design in clinics does not provide full comfort to the users and patients due to the impracticality, unergonomic, and unevolved designs. Aware of the needs and the importance of an attractive clinic design, a new identity and image of a new private clinic in a rural area is proposed. The collaboration among several experts in design and decoration has successfully projected a renewed design concept. The combination of interior and exterior decoration holds its own identity and uniqueness in attracting the attention of the local community. Among the elements researched are manufacturing, materials, and design. The design of this private clinic is an Islamic concept emphasizing important elements such as ergonomics, lighting, and workspace. Both physical and psychological elements are scrutinized to welcome patients or rural communities that come from various backgrounds and career landscapes. The latest materials such as steel, polyvinyl chloride (PVC) board, glass, concrete and wood are used in the interior design as well as the exterior of a premises. It aims to welcome and provide comfort to the rural community to experience the best health services while at the clinic. The proposed design covers all areas in the clinic, including a waiting room, treatment rooms or consultation rooms, toilets and other spaces available. The design of this clinic will give a new chapter in producing interior and exterior design for health premises and will provide a first-class atmosphere in welcoming rural communities to enjoy their own comfort while getting treatment at Mediklinik Al Waleed, Sungai Limau, Yan, Kedah.